FDG‐PET/CT‐guided rebiopsy may find clinically unsuspicious transformation of follicular lymphoma. (6th June 2022) - Rajamäki, Aino; Kuitunen, Hanne; Sorigue, Marc; Kokkonen, Salla‐Maarit; Kuittinen, Outi; Sunela, Kaisa
Abstract : Aim: The purpose of the study was to evaluate the clinical impact of fluorodeoxyglucose‐positron emission tomography/computed tomography (FDG‐PET/CT) followed by a new biopsy from the site with maximum standardized uptake value (SUVmax) in case of high maximal SUV values, in detecting clinically unsuspected histologic transformations (HT) of follicular lymphoma (FL). Methods: This retrospective study included all the patients who had undergone FDG‐PET/CT during primary diagnosis or relapse of FL between 2010 and 2020 at Oulu University Hospital. Results: The diagnosis changed from an indolent disease to a transformed lymphoma in >10% (7/63) of the patients who underwent diagnostic FDG‐PET/CT. The HT risk associated with high SUVmax (>10) was 24% (7 of 29 performed biopsies). Four out of these seven patients with verified HT had no previous clinical suspicion of transformation. Conclusion: Our results suggest that a rebiopsy based on a high SUVmax in diagnostic FDG‐PET/CT is valuable in detecting clinically unsuspected HT of FL. Abstract : Histologic transformation of follicular lymphoma often occurs locally in a limited number of disease sites and an indolent histology in a biopsy from one site does not exclude the presence of a high‐grade disease elsewhere. Our results suggest that a rebiopsy based on a high SUVmax in diagnostic FDG‐PET/CT is valuable in detecting HT after the diagnosis or relapse of follicular lymphoma